Hollow WO3/SnO2 Hetero-Nanofibers: Controlled Synthesis and High Efficiency of Acetone Vapor Detection - Shao, Hongyun; Huang, Minxuan; Fu, Hao; Wang, Shaopeng; Wang, Liwei; Lu, Jie; Wang, Yinghui; Yu, Kefu (Frontiers in Chemistry, 2019)
Metal oxide hetero-nanostructures have been widely used as the core part of chemical gas sensors. To improve the dispersion state of each constituent and poor stability existing in the heterogeneous gas sensing materials, uniaxial electro-spinning method combined with calcination was applied to synthesize pure SnO2 and three groups of WO3/SnO2 (WO3 of 0.1, 0.3, 0.9 wt%) hetero-nanofibers (HNFs) in our work. A series of characterizations prove that the products present hollow and fibrous structures composed of even nanoparticles and WO3 is uniformly distributed into SnO2 matrix. Gas sensing tests display that the sensor of WO3/SnO2 (0.3 wt%) not only exhibits the highest response (30.28) and excellent selectivity to acetone vapor at the lower detection temperature (170oC), 6 times higher than that of pure SnO2 (5.2), but still maintains considerable response (4.7) when the acetone concentration is down to 100 ppb with the corresponding response/recovery times of 25/286 s, respectively. Such structure obviously enhances the gas sensing performance towards acetone which guides the construction of highly sensitive acetone sensor. Meanwhile, the enhancement mechanism of such special sensor is also discussed in detail.